1982
DOI: 10.1126/science.7063870
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P-450-Dependent Monooxygenases in Olfactory Epithelium of Dogs: Possible Role in Tumorigenicity

Abstract: The respiratory tract epithelium of dogs, from the nose to the lungs, was examined for cytochrome P-450 and associated biotransformation activities. In the ethmoturbinates, where olfactory epithelium is located, the amount of cytochrome P-450 was comparable to that in the liver, when measured on the basis of activity per milligram of microsomal protein. The rest of the nasal region also contained large quantities of cytochrome P-450. The presence of these enzymes in the nose may be important in chemical-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(50 citation statements)
references
References 9 publications
2
48
0
Order By: Relevance
“…Sus and ensheathing glia derived apoE could be critically involved in recycling of membrane components liberated from the senescing ORN population and recycling it to support basal cell division and differentiation and axonal elongation of the newly differentiated ORN. We propose that Sus-derived apoE facilitates the various functions attributed to Sus and ensheathing glia (Barnett, 2004;Dahl et al, 1982;Getchell et al, 1984;Ramon-Cueto and Avila, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Sus and ensheathing glia derived apoE could be critically involved in recycling of membrane components liberated from the senescing ORN population and recycling it to support basal cell division and differentiation and axonal elongation of the newly differentiated ORN. We propose that Sus-derived apoE facilitates the various functions attributed to Sus and ensheathing glia (Barnett, 2004;Dahl et al, 1982;Getchell et al, 1984;Ramon-Cueto and Avila, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Luminal nonciliated cells in rodents, however, have abundant apical accumulations of agranula endoplasmic reticulum (aER), a feature not evident in similar cells in macaque monkeys. Relatively high amounts of cytochrome P-450-dependent monooxygenase (usually associated with aER) have been reported in the rat, rabbit, and dog nasal mucosa, covering the anterior nasal cavity (23,24). The anterior aspect of the dorsal concha of the dog nasal cavity, a region covered by TE, has recently been shown to have higher metabolizing activity for certain xenobiotic substrates than other regions of canine nasal mucosa (25).…”
Section: Nasal Epithelial Populationsmentioning
confidence: 99%
“…The latter studies were of particular importance since they suggested that agents reaching the nasal mucosa through the systemic circulation may be metabolically activated within target cells. Prior to 1982 when the group at Lovelace Inhalation Toxicology Research Institute first demonstrated the susceptibility of the rat and dog nasal mucosa to N-demethylate, a variety of cytochrome P-450 substrates, no other work had highlighted the potential importance of this tissue as a site for extrahepatic xenobiotic metabolism (8,9).…”
Section: Introductionmentioning
confidence: 99%